2015
DOI: 10.2220/biomedres.36.347
|View full text |Cite
|
Sign up to set email alerts
|

<b>Influence of neonatal sevoflurane exposure on nerve development-related microRNAs and behavior of </b><b>rats </b>

Abstract: Commonly used anesthetics adversely affect the developing brain, but the mechanisms remain unknown. We previously showed that the expressions of microRNAs (miRNAs) in major organs are affected by anesthetics. Therefore, we used TaqMan low-density array (TLDA) to analyze gene expression in the hippocampus of neonatal rats exposed to sevoflurane and performed behavioral tests after they reached adulthood to evaluate cognitive and memory function. Rat male pups at postnatal day 7 were exposed to 1.9% sevoflurane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…For example, Fujimoto et al . () reported changes in a number of nerve development‐related microRNAs, including rno‐miRNA‐632, mmu‐miR‐211 and mmu‐miR‐872, in the hippocampus of neonatal rats in response to sevoflurane exposure, leading to subsequent behavioural disorders. Lu et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fujimoto et al . () reported changes in a number of nerve development‐related microRNAs, including rno‐miRNA‐632, mmu‐miR‐211 and mmu‐miR‐872, in the hippocampus of neonatal rats in response to sevoflurane exposure, leading to subsequent behavioural disorders. Lu et al .…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that IGF-1 was an important factor to perfume sevoflurane Accumulating evidence has proven that the differential expression of miRNAs is induced by sevoflurane treatment. For instance, the exposure to sevoflurane during early neural development alters hippocampus-related miRNA expression thus inducing behavioral disorders (Fujimoto, Ishikawa, Nagano, & Sakamoto, 2015). MiR-125b and miR-181a were up-regulated in rat hippocampus treated with sevoflurane (Goto, Hori, Ishikawa, Tanaka, & Sakamoto, 2014).…”
Section: Igf-1 Inhibited the Positive Effect Of Sevoflurane On Tissue Necrosis And Apoptosismentioning
confidence: 99%
“…To date, the molecular mechanisms underlying sevoflurane-induced neurotoxicity have not been fully elucidated. However, a number of studies have demonstrated that exposure to sevoflurane induces alterations in the microRNA (miR) expression profile (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%